Sorption of heavy metals by humic acids of chestnut soils - Sabitova, A.N.; Bayakhmetova, B.B.; Mussabayeva, B.Kh.; Orazhanova, L.K.; Ganiyeva, K.G. (KSU Publ., 2020)
The purpose of this article is to study the sorption of heavy metals by humic acids of light and dark chestnut soil. The objects of research are the samples of dark and light chestnut soils, selected from an ecologically clean area of East Kazakhstan. Humic acids (HA) were separated from the soil at different pH values. At the same time the yield of HA was 0.075 % from dark chestnut soil at pH 1.0, and it was 0.017 % from light chestnut at pH = 7.0. Further, the dependence of the sorption degree on the medium acidity was established. It was found that zinc and cadmium are better sorbed in a strongly acidic medium (рН < 1.0; 84.14 %), while lead is preferably sorbed at pH 6.0, and the degree of its sorption is higher (93.54 %). It was established that metals have a mutual effect, suppressing or enhancing the sorption of each other in bi- and polyelement variants. It was shown that cadmium significantly suppresses lead sorption in neutral media. Zinc more often increases the sorption of both cadmium and lead by 3 times. It was concluded that the binding of heavy metal ions by the organic fraction of the soil occurs due to the complexation with humic acids.
Күрең топырақтың гумин қышқылдарының ауыр металдарды сорбциялауы
Сорбция тяжелых металлов гуминовыми кислотами каштановых почв
Keywords: heavy metals; dark chestnut soils; light chestnut soils (Kastanozems); organic fraction of soil; humic acids; sorption; zinc; lead; cadmium; East Kazakhstan; Borodulikha